Determination of Indicator Model of Cerebral Venous Thrombosis by Using Brachiocephalic Vessels Ultrasound Index of Arteriovenous ratio and Headache Visual Analogue Scale - Semenov, S.; Yurkevich, E.; Semenov, A. (Recent Developments in Medicine and Medical Research Vol. 15, 2021)
Verification of the venous nature of the lesion in some cases makes it possible to classify stroke and reduce the statistics of cryptogenic lesions. The importance of the venous stroke studying is also related to the fact that it develops at a younger age more often than the arterial stroke. Identification of signs of intracranial venous stasis using ultrasound methods in combination with determination of headache intensity according to the visual-analogue scale allows us to suspect the venous genesis of ischemic stroke before using neuroimaging methods, which can contribute to the selection of adequate therapy and to improve the prognosis and long-term outcomes of the disease. The purpose of this investigation is to search for confirmation of the hypothesis based on PCT according to which venous ischemia developing in cerebral venous sinustrombosis is secondary as a result of mechanical narrowing of arterioles in the area of vasogenic edema and plethora, which in its turn develops in the venous stroke earlier than in the arterial stroke against the background of the intracranial venous stasis. Objective: To study and determine the most prognostically significant rapid and available clinical and instrumental indicators on the model of early differential diagnosis of ischemic stroke of arterial and venous origin. Materials and Methods: Examined 124 patients with ischemic stroke: 22 with venous stroke due cerebral venous sinus thrombosis (VIS), 53.5 \(±\)16.7y and 102 with atherothrombotic stroke (AIS), 68.3 \(±\)12.1y which were verificated by native CT; CT-angiography, PCT (perfusion CT: CBF, CBV, MTT), brachiocephalic vessels ultrasound index of arteriovenous ratio (IAVR) and transcranial duplex scanning for all. IAVR was obtained due duplex scanning of carotid common arteries (CCA) and internal jugular veins (IJV) according to the formula: V max IJV optimal =2S CCA × Vps CCA/ 3S IJV (1) IAVR = max IJV actual / V max IJV optimal ×100%, where (2) IAVR – index of arteriovenous ratio, (%) Vps CCA – peak systolic velocity of the CCA, cm/s Vmax IJV – maximum blood flow velocity, cm/s. S – vessel cross-sectional area, cm2, as well as. To assess the neurological status of patients, rating scales were used, including a visually analog headache intensity scale. Results: The greatest prognostic significance was possessed by such parameters as the indicator of arteriovenous blood flow ratio and the value of headache intensity on a visual-analogue scale. A model for the differential diagnosis of AIS and VIS, which has high a specificity of 98% and a sensitivity of 95.2%, has been developed. Velocity indicators in the veins of Rosenthal and the vein of Galen are additional signs of intracranial venous stasis.